A gestão democrática na elaboração e implementação do plano diretor em municípios da região metropolitana de Maringá - Gaio, Adriana de Souza Ricardo (2014)
In order to contribute with studies about democratic management in the formulation of Public Policies, this work seeks investigating the instruments and mechanisms of control of democratic management established by the municipal master plan in the municipalities of the metropolitan region of Maringá, its attributions, practices and performance and the barriers to the full functioning of them. The democratic management in the development and implementation of the municipal master plan is crucial to its legitimacy and efficacy. The participation of the municipal administration technicians, as well as Executive Power, Legislative Power, collegiate organs and organized sector of civil society, in the stages of development, implementation, monitoring and social control, ensures to public managers conditions for its applicability and efficacy of its instruments, marks to federal, state and municipal organs the guidelines to the formulation of an Urban Development System, with the participation and social control of the actions, programmes and urban policy projects.